ANALISA DESIGN UI/UX POINT OF SALES BERBASIS WEB PADA RAJA SAMUDRA POPOK MENGGUNAKAN METODE DESIGN THINKING - Sanjaya, Andi; Mustika, Wida Prima; Rifai, Bakhtiar (Jurnal Manajamen Informatika Jayakarta, 2024)
Point Of Sale is a system for transactions, which includes the use of a cash register. Within the scope of POS, a cash register does not stand alone but includes supporting software and other devices. The Point of Sales application will help business owners to achieve goals and improve service to consumers. The time needed to serve consumers during sales transactions becomes faster and the information provided becomes more accurate. At Raja Samudra Popok, transactions and recording are still done manually with ledgers, including stock of raw materials which is still recorded using Microsoft Excel, which means the data is not always accurate. This research uses a user-oriented Design Thinking method. This method has 5 process stages, namely Emphatize, Define, Ideate, Prototype, and Testing. After carrying out these 5 stages well, the author then carried out usability testing using the System Usability Scale (SUS) method which resulted in an average score of 85. Based on the results of the SUS score interpretation, this value was included in grade A where the score obtained was already in above the average SUS score in general, which is 68.